The Gospel according to St Luke ; v. IV - Hastings, James , 1852-1922 (Aberdeen, Scotland "The Speakers Bible" Office., 1926)
Contents : v.IV : Luke ch. XX 9 - XXIV 53. Includes bibliographical references.
Keywords: Bible. N.T. Luke XX-XXIV -- commentaries